Recognition of a Drowning Victim by Bystanders: A Scoping Review (International Journal of First Aid Education)
Background: Globally, drowning is one of the leading causes of unintentional death. Whilst the World Health Organization (WHO) has identified that bystanders could play an important role in decreasing drowning deaths, few studies have evaluated whether bystanders can recognize a drowning victim. This scoping review aimed to identify common drowning characteristics to support bystanders in recognizing drowning. Method: Studies were identified through a systematic search of databases from the year 2000 until 2020, with the review guided by the PRISMA Scoping review process. Two hundred and nineteen potentially relevant articles were identified, of which 23 met all inclusion criteria. Results: There is limited to very limited empirical data describing how bystanders detect a distressed victim in the early stages of the drowning process. Implications: When preventative measures fail (drowning chain of survival step one), responders need to be able to perform the necessary steps to interrupt the drowning process. This study categorizes behaviors that may indicate that a person is in danger or in need of help in the water, which should support bystanders in recognizing someone in distress and the need to activate rescue and emergency medical services (drowning chain of survival step two and “early recognition" in the domain of first aid education). Conclusion: Whilst evidence is sparse, this review provides educators and training organizations with evidence-based behaviors which they can use to assist bystanders in understanding and identifying persons in danger or in need of help in the water.